Private and public control of management - Charles Angelucci; Martijn A. Han (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2012)
This paper investigates the design of a leniency policy to fight corporate crime. We explicitly take into account the agency problem within the firm. We model this through a three-tier hierarchy: authority, shareholder, and manager. The manager may breach the law and report evidence to the authority. The shareholder writes the manager's incentive scheme, monitors him, and possibly reports evidence to the authority. Finally, the authority designs a sanctioning/leniency policy that deters corporate crime at the lowest possible cost. The authority designs its policy trying to both (i) exacerbate agency problems within non-compliant firms and (ii) alleviate agency problems within compliant firms. We find that depending on the authority's ability to punish the manager, the authority may wish to instigate a within-firm race to the courthouse. We also provide comparative statics, carry a welfare analysis and discuss policy implications.
Keywords: K21; K42; L40; 330; corporate crime; white-collar crime; leniency; compliance; antitrust; Wirtschaftskriminalität; Straffreiheit; Prinzipal-Agent-Theorie; Corporate Governance; Konzentrationspolitik; Theorie